AvrBs3/PthA Virulence Factor of Bacterial Leaf Blight Race III, Race IV, Race VIII, and IXO93-068 - Utami, Dwinita W.; Kadir, Triny S.; Yuriyah, Siti (Jurnal AgroBiogen, 2011)
Bacterial leaf blight (BLB) is an important disease of rice and present throughout many of the rice-growing regions in the world, also in Indonesia. Xanthomonas oryzae pv. oryzae (Xoo) is the causal agent and a member of the Protebacteria and like many other this phyllum have a type III secretion system for protein virulence effector (PVE) released on their patho-genicity system. Commonly, PVE in Xanthomonas sp., is coded by AvrBs3/PthA family gene. This research was coducted to identify the virulence factor of AvrBs3/PthA on dominant Indonesian BLB isolates (Race III, Race IV, Ras VIII, and IXO93-068). This objective was obtained by sequence analysis through designed markers for members of the virulence factor AvrBs3/PthA gene family (PthXo4, avrXa7#38, PthXoS and avrXa7sacB50). Results gave infor-mation that RaceIII is a dependent elicitor race due to no PVE transcript formed and intraceluler protein target with RLL type on NLS (nuclear localization signal). RaceIV and RaceVIII are the virulent race which PVE active formed with intraceluler protein target and have the RLL and RLLP type for the NLS signal. While isolate IXO93-068 is a virulen isolate that active formed a PVE but the extraceluler protein target is due to no type of NLS. Based on cluster analysis, Race VIII has a genetic distance closely to PthXoS and avrXa7sacB50.